-Omics approaches to study and model cell-cell interactions in engineered tissues - Stark, Christine; Jenison, Sarah E.; Ngo, Mai T. (Frontiers in Chemical Engineering, 2025)
-Omics technologies have emerged as powerful tools to uncover cellular diversity within tissues, and the role of cell-cell communication in tissue development, function, and disease. In this review, we will discuss recent advancements in -omics technologies that are used to interrogate the biomolecular mechanisms that underly tissue form and function. We will specifically discuss the application of -omics technologies, along with bioinformatic tools, towards identifying new cell types and cell-cell interactions within native tissues. We will then examine how insights from -omics technologies can inform the design of engineered tissues, particularly through the lens of recapitulating native cell-cell interactions. Finally, we will discuss how -omics can be employed to benchmark and analyze engineered tissues for applications that span fundamental science and translation. Overall, the integration of -omics and tissue engineering will improve our understanding of the roles of cellular diversity and cell-cell communication in regulating tissue health and disease and subsequently inform how cell-cell interactions can be leveraged to design therapies for human health applications.